Management of Children in Dental Clinic during Covid-19 - N Sai Sri Harsha; Amit Agarwal; Md. Waseeullah; Sanjana Bhargava; Sadiya Tarannum; Aiman Haider (Journal of Orofacial Research, 2021)
Covid 19 (Corona virus disease), is a pandemic, which today’s world is going through. The first case was reported in the Wuhan City in December 2019, and then started spreading all over the world. The virus spreads through the droplets and also through direct contact, all the medical workers, especially dentists are at risk due to the mode of infection. The deadly corona virus has effected almost all ages, earlier it was found only to be infected for the old aged, but gradually evidence has proved that there is no low risk for even middle aged and children too. The impact of Covid has changed the way of dental practice, and the impact on pediatric dentistry is not reported much. The review is written focusing on the Covid 19 impact on pediatric dentistry, precautionary measures to be followed by a dentist and the children to lesser the chances of infection and transmission of virus. Scheduling appointments based on the emergency profile, Proper sterilization, disinfection of the dental clinic and instruments that are being used, Preliminary tests before appointment, Recording Medical history of the children, creating awareness among children and parents, other infection control measures. A pediatric dentist should be cautious, and be able to make the decisions suitably, and follow the proper guidelines in the Covid times to avoid infection for both self and the child.